Greenship Assessment of Indoor Health and Comfort at Greenhub Suited Offices - Rizka Rahmania; Dyah Nurwidyaningrum (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Implementation of Green Building can reduce global warming and create health and comfort workplace in order to improve employee performance. Greenhub Suited Office has the potential to get high points in achieving the Indoor Health and Comfort Aspect on the Greenship Interior Space 1.0. This research was done during work activities with 60% occupancy rate. This paper aims to analyze the achievements on indoor health and comfort aspect based on the Greenship rating tools Interior Space version 1.0. The descriptive approach on this reasearch was implemented by collecting data through the interview with an expert and occupants, literature study, the data retrieval with comparative study according to GBCI standard, fields survey directly, and field measurements. Based on the assessment, almost all the Indoor health and comfort criterias had been achieved by Greenhub Suited Offices. The results showed that Greenhub obtained a total index of 23 points with a percentage of 85%. Greenhub must earn 85% of Greenship Rating Tools percentage for the other five aspects on the GBCI standard to get a platinum rating.